Hubungan Dukungan Keluarga dengan Kebutuhan Spiritual pada Lansia di Desa Sampali Deli Serdang - Pomarida Simbolon; imelda Derang; Silvia Wulandari Hulu (Jurnal Riset Media Keperawatan, 2022)
Aging is a natural process that cannot be avoided, the older a person gets, the more spiritual they need. Spiritual needs are very important for humans, especially the elderly, because spirituality has a close relationship with the process of change and human development. This study aims to determine the relationship between family support and spiritual needs in the elderly at Sampali Deli Serdang Village 2022. The design of this study used observational analytic with a cross sectional approach. The sample in this study are 70 elderly people with a sampling technique using total sampling. Data collection is done directly by distributing questionnaires. The results of the study obtain that family support is (62.9%), high spiritual needs (67.1%). The results of the Chi-square test obtain p-value of 0.001 (<0.05) this indicates that there is a significant relationship between family support and spiritual needs in the elderly at Sampali Deli Serdang Village 2022. It is expected that families can perform worship once a week with invites religious leaders to get closer to the elderly to God Almighty.